Facile one-step synthesis of Ru doped NiCoP nanoparticles as highly efficient electrocatalysts for oxygen evolution reaction - Kim, Jun; Min Byeong-jo; Kwon, Taehyun; Kim, Taekyung; Song, Ho Chang; Ham, Hyung Chul; Baik, Hionsuck; Lee, Kwangyeol; Kim, Jin Young (WILEY-V C H VERLAG GMBH, 2021)
Transition metal phosphides (TMPs) as ever-evolving electrocatalytic materials have attracted increasing attention in water splitting reactions owing to their cost-effective, highly active and stable catalytic properties. This work presents a facile synthetic route to NiCoP nanoparticles with Ru dopants which function as highly efficient electrocatalysts for oxygen evolution reaction (OER) in alkaline media. The Ru dopants induced a high content of Ni and Co vacancies in NiCoP nanoparticles, and the more defective Ru doped NiCoP phase than undoped NiCoP ones led to a greater number of catalytically active sites and improved electrical conductivity after undergoing electrochemical activation. The Ru doped NiCoP catalyst exhibited high OER catalytic performance in alkaline media with a low overpotential of 281 mV at 10 mA cm(-2) and a Tafel slope of 42.7 mV dec(-1).